2019
DOI: 10.1108/ilt-07-2019-0258
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic effect of non-closed elliptical grooves of bi-directional rotation gas face seals

Abstract: Purpose The purpose of this paper is to improve opening performance of bi-directional rotation gas face seals by investigating the hydrodynamic effect of non-closed elliptical grooves. Design/methodology/approach A model of non-closed elliptical groove bi-directional rotation gas face seal is developed. The distribution of lubricating film pressure is obtained by solving gas Reynolds equations with the finite difference method. The program iterates repeatedly until the convergence criterion on the opening fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Profito and others studied the effect of surface texture on the tribological performance under the convergence gap through experiments and numerical analysis and found that the surface texture under the convergence gap can reduce the coefficient of friction by 10%–15% (Rosenkranz et al , 2019 ; Profito et al , 2015). Further, an investigation on face seals with spiral grooves and other textures found that the face thermal distortion developed a significant divergent clearance and convergent clearance, respectively; high speed enhanced this thermal distortion because of the downstream pumping effect of the spiral grooves (Bai et al , 2017; Xie et al , 2019). Furthermore, different surface textures have different heat transfer characteristics (Blasiak, 2015; Blasiak et al , 2013; Minkowycz and Haji-Sheikh, 2006); the sharp divergence distortion caused by the temperature difference between the inside and outside diameter is accompanied by a decrease in opening force and an increase in leakage rate (Bai and Wen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Profito and others studied the effect of surface texture on the tribological performance under the convergence gap through experiments and numerical analysis and found that the surface texture under the convergence gap can reduce the coefficient of friction by 10%–15% (Rosenkranz et al , 2019 ; Profito et al , 2015). Further, an investigation on face seals with spiral grooves and other textures found that the face thermal distortion developed a significant divergent clearance and convergent clearance, respectively; high speed enhanced this thermal distortion because of the downstream pumping effect of the spiral grooves (Bai et al , 2017; Xie et al , 2019). Furthermore, different surface textures have different heat transfer characteristics (Blasiak, 2015; Blasiak et al , 2013; Minkowycz and Haji-Sheikh, 2006); the sharp divergence distortion caused by the temperature difference between the inside and outside diameter is accompanied by a decrease in opening force and an increase in leakage rate (Bai and Wen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this result may be that, with the increase in clearance, the shear rate of the fluid decreases, which leads to a decreasing of the upstream pumping effect, such that the gas leakage increases and the liquid leakage rate decreases. However, the result of the inclined angle α = 45° had a more significant upstream pumping effect than that of α = −45° and α = 0°, which led to a larger backward liquid leakage rate and a larger hydrodynamic opening force, as discussed in [26,27].…”
Section: Seal Clearancementioning
confidence: 94%
“…In 2008, Lebeck 's work [16] showed that "gas seal oil" between low pressure air and high pressure oil could achieve zero leakage with the design of upstream pumping linear grooves, and the experiment confirmed that the feasibility of the mutual sealing of the gas phase and liquid phase fluid. The theoretical analysis [7,[15][16][17] proved that the inclined elliptical dimples could not only present enough upstream pumping effect to realize the complete reverse leakage of sealed medium, but also generate obvious dynamic pressure effect to keep the non-contact operation of sealing faces, which could provide another feasible way for the design of upstream pumping sealing faces.…”
Section: Introductionmentioning
confidence: 99%